IDENTIFIKASI FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT USAHATANI JAGUNG MANIS DI DESA SEBEMBAN KECAMATAN MUARA WIS (Identification of Factors Affecting Interest in Sweet Corn Farming in Sebemban Village, Muara Wis Subregency) - FETI RAHMAH; RITA MARIATI; SYARIFAH MARYAM (Universitas Mulawarman (University of Mulawarman), 2021)
The aims of this research were to identify the push and pull factors that affect farmers interest in sweet corn farming. The research was conducted from June to August 2020 in Sebemban Village, Muara Wis, Subregency, Kutai Kartanegara Regency by doing survey. The number of samples in this study were 31 sweet corn farmers. Data was analysed by using descriptive method. The results of identification showed that the push factors of farmers interest in sweet corn farming are age, education, land area, experience, and number of dependents. The pull factors of farmers interest in sweet corn farming are the role of extension worker, income, and marketing.